The Effects of Illness Perception on Diet Adherence in Patients With Hypertension - Leila Rouhi Balasi; Arsalan Salari; Abdolhosein Emami Sigaroudi; Asieh Ashouri; Fatemeh Moaddab; Fatemeh Zaer Sabet; Azam Nourisaeed (Caspian Journal of Health Research, 2021)
Background: The role of nutrition is undeniable in controlling hypertension; diet is among the most effective non-pharmaceutical methods. The current study aimed to determine the role of illness perception on diet adherence in patients with hypertension. Materials & Methods: This cross-sectional study examined 268 patients with hypertension. The study sample was selected by convenience sampling method. The study tool consisted of the patients’ individual, social, and clinical factors, illness perception about hypertension, and adherence to the diet. The necessary data were analyzed using multiple logistic regression models. Results: The Mean±SD score of illness perception was measured as 37.09±4.91 out of 56. Adherence to the recommended diet was relatively desirable in the majority of the examined patients (62%). Multiple logistic regression analysis data revealed no significant relationship between the scores of illness perception and dietary adherence (Adjusted OR=1.038, 95%CI: 0.974-1.105, P =0.250). The main predictor of dietary adherence was having hypertension dietary knowledge (OR=2.198, 95%CI: 1.198-4.035, P=0.011). Conclusion: Our study data revealed that increasing awareness among patients with hypertension complications can improve self-care behaviors, including adherence to standard diets. Therefore, emphasis on increasing awareness among these patients and their continued follow-up seems necessary.